A Comparative Study of the Level of Mental Health and Its Correlation to the Skill of Spike of the Players of Education Teams in Baghdad Karkh Volleyball - Abd Ulsattar, aher Abd Ulelah (International Journal of Psychosocial Rehabilitation, 2020)
Since the beginning of interest in the study of mental health a short time ago, however, psychology has achieved success in understanding human behavior as man seeks to achieve the best in terms of physical and mental health and mental health, where he is faced in daily life multiple psychological pressures and lead to psychological and physical disorders. As for the sports field and in the game of flying ball, the mental health of the individual sports is important in the exercise of the activity of the athlete and the performance of sports exercises, whether in training or sports practices and the development of mental, physical, skill and psychological capacity as sport is closely related to the improvement of mental health and the emergence of positive emotional feelings and enjoyment of psychological happiness Many studies are done by promoting self-confidence and improving a good outlook by relieving stress.